2015
DOI: 10.1007/s00395-015-0480-y
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-27, a novel cytokine induced by ischemia–reperfusion injury in rat hearts, mediates cardioprotective effects via the gp130/STAT3 pathway

Abstract: Patients with coronary artery disease show high serum levels of interleukin (IL)-27, a novel member of the IL-6 family. However, the function of IL-27 in hearts suffering ischemia/reperfusion (IR) injury is unclear. Here, we showed increased expression of mRNA for the IL-27 subunits, EBI3 and p28, in rat hearts after 40 min of coronary ligation and release for 7 days. This increase was associated with a peak in the release of the cardiac enzyme, creatine kinase-MB, on day 2 post-release. Moreover, levels of IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…In IL-27-deficient (Ldlr 94 . In addition, in a rat model of ischemia/reperfusion injury, IL-27 administered 5 minutes before reperfusion reduced tissue damage and markedly improved post-ischemia recovery in isolated perfused hearts; this finding suggests that this cytokine protects the myocardium against ischemia/reperfusion injury, thus facilitating the recovery of damaged cardiomyocytes 95 . In an in vitro study, it has been demonstrated that IL-27 decreased lipid accumulation in THP-1 derived macrophages and markedly enhanced cholesterol efflux through increasing the expression of both ABCA1 mRNA and protein 96 .…”
Section: Il-27mentioning
confidence: 88%
“…In IL-27-deficient (Ldlr 94 . In addition, in a rat model of ischemia/reperfusion injury, IL-27 administered 5 minutes before reperfusion reduced tissue damage and markedly improved post-ischemia recovery in isolated perfused hearts; this finding suggests that this cytokine protects the myocardium against ischemia/reperfusion injury, thus facilitating the recovery of damaged cardiomyocytes 95 . In an in vitro study, it has been demonstrated that IL-27 decreased lipid accumulation in THP-1 derived macrophages and markedly enhanced cholesterol efflux through increasing the expression of both ABCA1 mRNA and protein 96 .…”
Section: Il-27mentioning
confidence: 88%
“…Male SD rats were anesthetized with sodium pentobarbital (45 mg·kg −1 , i.p.). The heart was rapidly excised and retrogradely perfused through the aorta by a Langendorff perfusion system with oxygenated KHB (Ma et al ., ), containing 120 mM NaCl, 4.7 mM KCl, 1.25 mM CaCl 2 , 25 mM NaHCO 3 , 1.2 mM KH 2 PO 4 , 1.2 mM MgSO 4 and 11 mM glucose (pH 7.4), with a constant pressure of 80 mm Hg at pH 7.4 bubbled with 95% O 2 /5% CO 2 at 37°C (Wang et al ., ). To establish the I/R injury model, isolated, perfused rat hearts were subjected to 40 min of ischaemia followed by 60 min of reperfusion.…”
Section: Methodsmentioning
confidence: 99%
“…32 Interleukin-27 (IL-27), a recently discovered member of the IL-6 family, is elevated in patients with coronary heart disease. 33 IL-27 was proved to activate STAT3 by receptor subunit gp130, and this activation was reversible with application of a gp130-neutralizing antibody in rodent hearts. IL-27 and IL-6 were shown to remarkably limit cell damage after induction of severe hypoxia in H9c2 cardiomyoblasts and primary rat neonatal cardiomyocytes by appreciation of lactate dehydrogenase release and crystal violet staining in experimentally induced ischemia/reperfusion (IR) injury.…”
Section: The Therapeutic Implications Of Stat Proteins -Current Statementioning
confidence: 99%
“…IL-27 and IL-6 were shown to remarkably limit cell damage after induction of severe hypoxia in H9c2 cardiomyoblasts and primary rat neonatal cardiomyocytes by appreciation of lactate dehydrogenase release and crystal violet staining in experimentally induced ischemia/reperfusion (IR) injury. 33 Before discussing the relationships of STAT3 with pharmacological agents, it is worth noting what STAT3 has in common with "sports". 34 STAT3 plays a role in the prophylaxis and prevention of cardiac insufficiency with linkage to physical exercise.…”
Section: The Therapeutic Implications Of Stat Proteins -Current Statementioning
confidence: 99%